What happens to the body when one works at night? - Claudia Roberta de Castro Moreno; Fernando Mazzilli Louzada
The objective of this paper is to present some recent chronobiological findings related to shift and night worker adaptation. First, some key chronobiological concepts concerning the human species are presented. The authors then discuss the possible impacts of work schedules on shift workers' and night workers' health. Finally, countermeasures that might allow adjusting the workers' biological rhythm to shift and night work are discussed.